Option A
-x + 6y = 42 is the standard form
Solution:
Given that we have to write
in standard form
The standard form of an equation is Ax + By = C
In this kind of equation, x and y are variables and A, B, and C are integers
Given equation is:
![y = (1)/(6)x+7](https://img.qammunity.org/2021/formulas/mathematics/middle-school/6t8bm0ya8w4ecity154q2sgz1rlpot8kfh.png)
Let us convert the above equation into standard form
![y = (x)/(6) + 7](https://img.qammunity.org/2021/formulas/mathematics/middle-school/7l3axjttc4ojxwe7acocpi1yw0vegpil0x.png)
![y = (x)/(6) + (7)/(1)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/utegf0py6d78fyb3b3eizbkfyeoxholfa6.png)
Make the denominator same in R.H.S
![y = (x)/(6) + (7 * 6)/(1 * 7)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/ktl5c8oricxqgh68ag1k59akhxn7kjcyrg.png)
Solve the above equation
![y = (x)/(6) + (42)/(6)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/gqily9rxul8ks45m9jontv1gnib8qspjj1.png)
![y = (x+42)/(6)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/ovosqcxutqd25h2rkrkta3xaoxm6leohkt.png)
Move 6 from R.H.S to L.H.S
![6y = x + 42](https://img.qammunity.org/2021/formulas/mathematics/middle-school/mu7quv71p71t8bcjm89zq95nvd5r2d20q5.png)
Bring all the terms to one side, leaving only constant on R.H.S
![-x + 6y = 42](https://img.qammunity.org/2021/formulas/mathematics/middle-school/szz9xu4lvps1p578ua78xvsqei4i81wt0s.png)
The above equation is of form Ax + By = C
Thus option A is correct